The Fucoxanthin Chlorophyll a/c-Binding Protein in Tisochrysis lutea: Influence of Nitrogen and Light on Fucoxanthin and Chlorophyll a/c-Binding Protein Gene Expression and Fucoxanthin Synthesis - Pajot, Anne; Lavaud, Johann; Carrier, Gregory; Garnier, Matthieu; Saint-Jean, Bruno; Rabilloud, Noémie; Baroukh, Caroline; Bérard, Jean-Baptiste; Bernard, Olivier; Marchal, Luc; Nicolau, Elodie (Frontiers in Plant Science, 2022)
We observed differences in lhc classification among Chromista. We proposed a classification of the lhcf family with two groups specific to haptophytes, one specific to diatoms, one specific to seaweeds. The identification and characterization of the fucoxanthin and chlorophyll a/c-binding protein (FCP) of the haptophyte microalgae Tisochrysis lutea was performed using similarity analysis. The FCP family contains 52 lhc genes in T. lutea. The FCP pigments binding sites were characterized on the Lhcf protein monomers of T. lutea, which possesses at least nine chlorophylls and five fucoxanthin molecules in average per monomer. The expression of T. lutea lhc genes was assessed during turbidostat and chemostat experiments, one with constant light and changing nitrogen phases, the second with a 12 h: 12 h (day:night) sinusoidal photoperiod and changing nitrogen phases. RNAseq analysis of the 52 lhc sequences revealed a dynamic decrease in the expression of genes with nitrogen depletion. The day:night cycle expression revealed T. lutea lhcx2 is only expressed at night, suggesting that its role is to protect the cells from the return of the light after a prolonged darkness exposure.